CHANGES IN THE CD4 COUNTS, HEMOGLOBIN AND BODY WEIGHT IN PATIENTS WITH HIV ALONE AND HIV- TB CO-INFECTION - KR, DINAKAR; SANJI, NARENDRANATH; VANEET AGGARWAL; SR, RESHMA; SOMASHEKAR HS; J, KEERTHISAGAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives:Â To assess the changes in the CD 4 counts, hemoglobin and weight in patients co-infected with HIV/Tb receiving anti-retroviral therapy and anti-tubercular therapy. To compare the changes of these parameters between the group receiving ART alone and the group receiving ART and ATT. Methodology: Retrospective data was collected from the ART centre, Chigateri Hospital, Davangere, Karnataka. Patients on any one HAART regimen for atleast six months were compared against patients receiving both HAART and ATT. Changes in the CD4 counts, hemoglobin levels and weight were analyzed with statistical tests. Results: Data from the records of 506 HIV patients were analyzed out of which 90 had tuberculosis. There was a significant improvement in the CD4 counts of both the groups with treatment (HIV:p=0.0001; co-infection:p=0.0001) but the mean improvement did not vary in either groups (HIV:138.71 cells; co-infection:138.58 cells). The hemoglobin did not improve significantly in either group (HIV:p=0.2485; co-infection:p=0.2966) but the mean hemoglobin improvement in the HIV alone group was better (HIV:2.69g%; co-infection:0.41g%). There was an improvement of weight in both the groups with treatment (HIV:p=0.042;co-infection:p=0.0004) but the mean weight improvement was better in co-infection group (HIV:1.86kgs; co-infection:3.36kgs). Conclusion: In our study all the parameters improved in both the groups. Presence of Tb did not influence the improvement in CD4 counts. The weight improved significantly in both the groups, which was very significant in the co-infection group. The rise in the hemoglobin levels was not statistically significant. Â Key words: CD4 counts, Hemoglobin, Body Weight, HIV-TB coinfection.